Qualidade tecnológica e sensorial de apresuntados elaborados com carnes PSE e RFN e diferentes concentrações de sal - Paula, Marielle Maria de Oliveira (2018)
With the current need for sodium reduction, together with the incidence of PSE meat in slaughterhouses in Brazil, the objective of this study was to evaluate the technological and sensorial quality of prepared fish with PSE and normal meat (RFN) and different concentrations of salt(0.8%, 1.2%, 1.6%, 2.0% and 2.4%). The water activity (Aw) was reduced (P<0.05) when the salt was added with different behaviors for the meat types. The values for cooking loss (PPC) andexpressive moisture (PEX) increased (P<0.05) as the salt content was decreased. The hardness presented lower values (P<0.05) with the salt reduction, and the presented PSE restructured cooked hams greater flexibility and less cohesiveness when compared to the RFN. The fracture energy was higher (P<0.05) restructured cooked hams in the RFN than the PSE. For the redness (a*) and yellowness (b*) the salt reduction increased (P<0.05) the values in redness while the use of PSE meat increased the values in redness and reduced (P< 0,05) the values of yellowness. The coordinates of chroma (C*) was affected (P<0.05) by the salt, its reduction implied in the color of the more intense samples; already the type of meat affected the hue angle (h*), where the restructured cooked hams PSE presented a reduced tone. The saltiness was higher in the products elaborated with PSE meat than with normal meat. Although there was a higher preference for the elaborated samples with higher salt content (2.0 to 2.4%), the judges preferred the samples made with PSE meat when smaller concentrations of salt (<1.6%) were used. A sensorial profile characterization was also carried out on the restructured cooked hams of normal meat (RFN) and PSE and the salt levels 1.2%, 1.6% and 2.0%, which were determined from the first experiment. Lower salt content (P<0.05) resulted in higher acceptance scores for the flavor and overall impression, and PSE meat samples were (P <0.05) more accepted for the overall impression of the products. Through the CATA methodology, it was observed that the sample PSE 1,2%, presented as descriptors terms " flavor characteristic of restructured cooked hams”, "juicy" and “tenderness”,which may have contributed positively to its acceptance, however, the samples RFN 2.0% and 1.6¨%, were related to the terms of textures as "boring" and "tough ", negatively affecting their a cceptance , which could be observed through the internal preference maps of the attributes.In the TDS, the "flavor characteristic of restructured cooked hams" was always reported at the beginning of the tasting, followed by the "saltiness" in the samples with 1.6% or more salt or the "residual flavor" or "meat flavor" in the samples with 1,2% salt. In general, in order to achieve the salt reduction goals together with the use of PSE meat in meat products, it is concluded that the addition of salt in the 1.2% range along with the PSE meat in the restructured cooked hams ones proved to be beneficial, with changes in the technological quality of those present and with a good response to their sensorial profile.